Preparation method and application of polyanionic material with coexistence of crystalline phase and amorphous phase

The carbon-covered polyanionic electrode material prepared by high-temperature melting-quenching-ball milling-secondary baking process solves the life problem caused by the crystal structure changes of lithium-ion batteries at high voltage, and achieves efficient ion diffusion and low-temperature performance promote.

CN116262608BActive Publication Date: 2024-12-20DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111536804.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-15
Publication Date
2024-12-20
Estimated Expiration
2041-12-15

AI Technical Summary

Technical Problem

The crystal structure changes of existing lithium-ion battery materials at high voltages lead to a shortening of cycle life, and the intrinsic electronic conductivity of the material is low, limiting its application performance.

Method used

Using high-temperature melting-quenching-ball milling-second calcining-fast cooling technology, polyanionic electrode materials with crystal phase and amorphous phase coexisting are prepared. By coating material particles by carbon, rich grain boundaries are formed to improve ion diffusion. rate.

Benefits of technology

It significantly improves the rate performance and low temperature performance of lithium-ion or sodium-ion batteries, extends the cycle life of the battery, and stabilizes the structure of the material during charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003413295750000011
    Figure HDA0003413295750000011
  • Figure HDA0003413295750000012
    Figure HDA0003413295750000012
Patent Text Reader

Abstract

The present invention belongs to the field of alkali metal batteries, and particularly relates to a preparation method and application of a polyanionic material in which a crystalline phase and an amorphous phase coexist. A preparation method of a polyanionic material comprises mixing raw materials containing an alkali metal source, a transition metal source, and an anion source, and calcining to obtain a molten precursor; quenching the molten precursor to obtain amorphous phase particles; mixing the amorphous phase particles with a carbon source, and ball milling to obtain a mixture; and calcining the mixture in an inactive atmosphere to obtain the polyanionic material. The battery electrode material prepared by the method has abundant crystal plane boundaries, high ion diffusion rate, excellent rate performance, and high and low temperature performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of alkali metal batteries, and particularly relates to a method for preparing a polyanionic material in which a crystalline phase and an amorphous phase coexist. Background Art

[0002] Lithium-ion batteries have the advantages of high working voltage, high specific energy, and good cycle life. Whether it is consumer lithium-ion batteries, power batteries, or large-scale energy storage batteries, they have been mass-produced and applied. At present, due to the growing demand, lithium-ion batteries have exposed the scarcity of resources such as lithium, cobalt, and nickel, and the rising prices of raw materials. Sodium-ion batteries have similar working principles to lithium-ion batteries, but sodium resources are abundant and low in cost. As a beneficial supplement to lithium-ion batteries, they have broad application prospects in the fields of low-speed electric vehicles and large-scale energy storage. Polyanion-type lithium and sodium electrode materials, as a type of active material for lithium and sodium-ion battery electrodes, have abundant raw material resources, do not contain rare precious metals, are low in cost, and have stable crystal structures. The "inductive effect" in polyanion compounds makes polyanion electrode materials have a higher working voltage. Therefore, the development of high-performance polyanion-type lithium and sodium-ion battery electrode materials and the enrichment of energy storage battery electrode materials are of great significance to the development and application of energy storage batteries.

[0003] The polyanionic material with NASCION structure has a fast channel for lithium ion migration inside, and has the advantages of high stability, long cycle life, excellent rate performance, high voltage platform, etc. However, the intrinsic electronic conductivity of the polyanionic material is low, and when used in a high voltage range, the change in the crystal structure of the material will shorten the cycle life of the battery. The present invention proposes a preparation method for a polyanionic material in which a crystalline phase and an amorphous phase (glass phase) coexist by "high temperature melting-secondary calcination crystallization". The prepared electrode material has abundant grain boundaries and has excellent rate performance and low temperature performance when applied to lithium ion batteries and sodium ion batteries. Summary of the invention

[0004] The present invention is to improve the performance of polyanionic electrode materials, and proposes a method for preparing a polyanionic material in which a crystalline phase and an amorphous phase coexist. A polyanionic electrode material in which a crystalline phase and an amorphous phase (glass phase) coexist is prepared by a "high temperature melting-quenching-ball milling-secondary roasting-rapid cooling" process, and the primary particles of the material are composed of an orderly arranged crystal structure and a disordered arranged amorphous structure, as well as a carbon layer coated on the surface of the material particles. The polyanionic material prepared by the method has abundant crystal plane boundaries, a high ion diffusion rate, and excellent rate performance and high and low temperature performance.

[0005] On the one hand, the present invention provides a method for preparing a polyanionic material:

[0006] Step (1), mixing raw materials containing an alkali metal source, a transition metal source, and an anion source (the raw materials are weighed according to the molar ratio of the elements of the target polyanionic material), and calcining to obtain a molten precursor;

[0007] Step (2), quenching the molten precursor to obtain amorphous particles;

[0008] Step (3), mixing the amorphous phase particles with a carbon source, and ball milling to obtain a mixture;

[0009] Step (4), calcining the mixture in an inactive atmosphere to obtain the polyanionic material.

[0010] Optionally, the polyanionic material is composed of (X m O 3m+1 ) n- MO of anionic unit and polyhedral unit s and cationic units.

[0011] Optionally, the cationic unit is an alkali metal ion.

[0012] Optionally, the (X m O 3m+1 ) n- In the anion unit, X is selected from any one of S, P, Si, As, and Mo; m=1 or 2; and n=3 or 4.

[0013] Optionally, the MO of the polyhedral unit s In the above, M is selected from at least one transition metal element; the transition metal is selected from V, Mn, Fe, Ti, Cr; and s is an integer between 4 and 8.

[0014] Optionally, the (X m O 3m+1 ) n- The anion unit is (PO4) 3- or (P2O7) 4- ;

[0015] Optionally, the alkali metal ion is selected from Na + , Li + or K + .

[0016] Optionally, in step (1), the molar ratio of the amount of alkali metal in the alkali metal source, the amount of transition metal in the transition metal source, and the amount of X in the anion source is calculated based on the molar ratio of the alkali metal element, the transition metal element, and X in the obtained polyanionic material.

[0017] Optionally, the alkali metal source is selected from at least one of carbonates, nitrates, acetates, fluorides, pyrophosphates, hydrogen pyrophosphates, and hydroxides.

[0018] Optionally, the alkali metal compound is selected from at least one of sodium carbonate, sodium bicarbonate, sodium nitrate, sodium hydroxide, sodium acetate, disodium hydrogen phosphate, sodium pyrophosphate, sodium hydrogen pyrophosphate, sodium fluoride, lithium carbonate, lithium nitrate, lithium hydroxide, lithium acetate, lithium phosphate, and lithium fluoride.

[0019] Optionally, the transition metal source is selected from at least one of vanadium pentoxide, vanadium trioxide, vanadium dioxide, ammonium metavanadate, vanadium oxalate, vanadium phosphate, manganese dioxide, manganese pentoxide, titanium dioxide, ferric oxide, ferric oxalate, ferrous acetate, ferrous chloride, chromium oxide, sodium dichromate, chromium oxalate, and chromium acetate.

[0020] Optionally, the anion source is selected from at least one of phosphoric acid, pyrophosphoric acid, ammonium hydrogen phosphate, ammonium pyrophosphate, ammonium hydrogen pyrophosphate, diammonium phosphate, lithium silicate, sodium silicate, and silica gel.

[0021] Optionally, the calcination temperature is 900-1150°C, the lower limit of the calcination temperature is selected from 900°C and 1000°C, and the upper limit is selected from 1000°C and 1150°C; the insulation time is 1-10h.

[0022] Optionally, in step (2), the cooling rate of the quenching is ≥80°C / min, preferably 80°C to 100°C / min; preferably, the temperature is reduced to room temperature, and preferably, the time from the calcination temperature to room temperature is within 10 minutes.

[0023] Optionally, the quenching is performed by pouring the molten precursor into a quenching liquid.

[0024] Optionally, the quenching liquid is water at room temperature.

[0025] Optionally, in step (3), the carbon source is selected from at least one of citric acid, starch, glucose and sucrose.

[0026] Optionally, the amount of the carbon source is 15% to 45% of the amount of the amorphous phase particles, and the lower limit of the percentage of the carbon source in the amorphous phase particles is selected from 15% and 30%, and the upper limit is selected from 30% and 45%.

[0027] Optionally, the ball milling time is 6 to 18 hours, the lower limit of the ball milling time is selected from 6 hours and 10 hours, and the upper limit is selected from 10 hours and 18 hours; preferably, the amorphous phase particles are dried before the ball milling, and the drying temperature is preferably 100°C.

[0028] Optionally, in step (4), the heating rate of the roasting is 8-20 °C / min. The lower limit of the heating rate of the roasting is arbitrarily selected from 8 °C / min and 15 °C / min; the upper limit is arbitrarily selected from 15 °C / min and 20 °C / min; the roasting temperature is 700-1000 °C. The lower limit of the roasting temperature is arbitrarily selected from 700 °C and 800 °C, and the upper limit is arbitrarily selected from 800 °C and 1000 °C; the holding roasting time is 1-4 h. The lower limit of the holding roasting time is arbitrarily selected from 1 h and 2 h, and the upper limit is arbitrarily selected from 2 h and 4 h; the cooling rate after the holding is ≥40 °C / min. The lower limit of the cooling rate is arbitrarily selected from 40 °C / min and 80 °C / min, and the upper limit is arbitrarily selected from 80 °C / min and 100 °C / min; it is preferably cooled to room temperature.

[0029] Optionally, the inert atmosphere is argon.

[0030] Optionally, the particle size of the primary particles obtained in step (4) is 0.2-15 μm.

[0031] On the other hand, the present invention provides a polyanion-type material obtained by any of the above preparation methods.

[0032] Optionally, the polyanion-type material is selected from sodium vanadium phosphate (Na3V2(PO4)3), sodium manganese phosphate (NaMnPO4), sodium iron phosphate (NaFePO4), sodium titanium phosphate (NaTi2PO4), sodium vanadium difluorophosphate (Na3V2(PO4)2F3), sodium iron difluorophosphate (Na5Fe2(PO4)2F3), sodium manganese difluorophosphate (Na5Mn2(PO4)2F3), sodium iron fluorophosphate (Na2FePO4F), sodium manganese fluorophosphate (Na2MnPO4F), sodium vanadium fluorophosphate (NaVPO4F), sodium iron pyrophosphate (Na2FeP2O7), sodium iron pyrophosphate phosphate (Na4Fe3(P2O7)(PO4)2), sodium manganese pyrophosphate (Na2MnP2O7), sodium manganese pyrophosphate phosphate (Na4Mn3(P2O7)(PO4)2), sodium manganese silicate (Na2MnSiO4), sodium iron silicate (Na2FeSiO4), lithium vanadium phosphate (Li3V2(PO4)3), lithium manganese vanadium phosphate (Li4MnV(PO4)3), lithium titanium phosphate (LiTi2PO4), lithium vanadium fluorophosphate (LiVPO4F), lithium manganese silicate (Li2MnSiO4), sodium iron vanadium phosphate (Na4Fe x V (2-x) (PO4)3, where 0 < x < 2), sodium manganese vanadium phosphate (Na4Mn x V (2-x) (PO4)3, where 0 < x < 2), sodium iron vanadium fluorophosphate (Na4Fe x V (2-x) (PO4)2F3, where 0 < x < 2), sodium manganese vanadium fluorophosphate (Na4Mnx V (2-x) (PO4)2F3, where 0 < x < 2), sodium vanadium manganese iron phosphate (Na4V a Mn b Fe 2-a-b (PO4)3, where 0 < a < 2, 0 < b < 2, 0 < a + b < 2), sodium vanadium iron manganese fluorophosphate (Na4V a Mn b Fe 2-a-b (PO4)2F3, where 0 < a < 2, 0 < b < 2, 0 < a + b < 2), sodium manganese iron fluorophosphate (NaMn d Fe 1-d PO4F, where 0 < d < 1), sodium vanadium iron manganese fluorophosphate (NaV e Mn f Fe 1-e-f PO4F, where 0 < e < 1, 0 < f < 1, 0 < e + f < 1), sodium manganese iron pyrophosphate (Na2Mn x Fe 2-x P2O7, where 0 < x < 2), sodium vanadium iron manganese pyrophosphate (Na2V x Mn y Fe 2-x-y P2O7, where 0 < x < 2, 0 < y < 2, 0 < x + y < 2), sodium manganese iron phosphate pyrophosphate (Na4Mn x Fe 3-x (P2O7)(PO4)2, where 0 < x < 3), sodium vanadium iron manganese phosphate pyrophosphate (Na4V x Mn y Fe 3-x-y (P2O7)(PO4)2, where 0 < x < 3, 0 < y < 3, 0 < x + y < 3), sodium manganese iron silicate (Na2Mn x Fe 1-x SiO4, where 0 < x < 1), sodium vanadium iron manganese silicate (Na2V x Mn y Fe 1-x-y SiO4, where 0 < x < 1, 0 < y < 1, 0 < x + y < 1) or at least one of them.

[0033] Optionally, there are amorphous structures with disordered arrangements and crystalline structures with ordered arrangements in the polyanionic material; preferably, the mass ratio of the crystalline structure in the polyanionic material is 50-90%; the surface of the polyanionic material is coated with carbon; the particle size of the polyanionic material is 0.2-15 μm.

[0034] In another aspect, the present invention provides an alkali metal battery positive electrode material, wherein the alkali metal battery positive electrode material contains the polyanionic material obtained by any of the above preparation methods; or the alkali metal battery positive electrode material contains any of the above polyanionic materials; the alkali metal battery is a lithium ion battery, a sodium ion battery or a potassium ion battery.

[0035] Optionally, in the alkali metal battery positive electrode material, the percentage of the polyanionic material is 85% to 98%.

[0036] The lithium vanadium phosphate positive electrode material with coexistence of crystalline phase and amorphous phase proposed by the present invention has the following obvious advantages:

[0037] (1) The obtained polyanion material has an ordered crystalline structure and a disordered amorphous structure, as well as a carbon layer coating on the surface of the material particles;

[0038] (2) The polyanionic electrode material prepared by this method has abundant crystal boundaries, which serve as channels for lithium ions or sodium ions to escape and embed into the material, and can improve the diffusion rate of lithium ions or sodium ions. The material has good rate performance and excellent low-temperature performance.

[0039] (3) The amorphous phase region is filled between the crystalline phase regions, which can weaken the strain caused by the change of the crystal structure and stabilize the structure of the material during the charging and discharging process.

[0040] The outstanding advantage of the present invention is that it realizes the preparation of polyanionic electrode materials in which carbon-coated crystalline phase and amorphous phase coexist, regulates the secondary calcination crystallization process and the nucleation and growth process of the crystal, and obtains a two-phase coexisting polyanionic electrode material with rich grain boundaries, thereby improving the performance of polyanionic lithium-ion batteries or sodium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a TEM photo of the carbon-coated lithium vanadium phosphate material 1# prepared in Example 1;

[0042] Figure 2 This is a TEM photograph of the pure crystalline lithium vanadium phosphate material A prepared in Comparative Example 1. DETAILED DESCRIPTION

[0043] The advantages of the present invention are further described below in conjunction with specific implementation methods.

[0044] Example 1 Preparation of a two-phase polyanionic compound lithium vanadium phosphate (Li3V2(PO4)3)

[0045] The polyanionic compound prepared in this embodiment is lithium vanadium phosphate (Li3V2(PO4)3), which is composed of 3 anion units, 3 cation units and 2 polyhedral units; wherein the anion unit is (PO4) 3- , polyhedral unit is VO s ,; the cationic unit is Li.

[0046] The preparation steps of the polyanionic compound are:

[0047] Step (1), accurately weighing 32.52 g of lithium hydroxide monohydrate, 72.96 g of vanadium phosphate, and 28.76 g of ammonium dihydrogen phosphate, mixing them evenly and adding them into a corundum crucible, then placing the crucible in a muffle furnace and heating it to 1000° C., and calcining to obtain a molten lithium vanadium phosphate precursor;

[0048] Step (2), pouring the molten lithium vanadium phosphate precursor of step (1) into deionized water at room temperature for quenching, cooling from 1000° C. to room temperature within 10 minutes, to obtain amorphous (glassy) lithium vanadium phosphate precursor particles;

[0049] Step (3), drying the glassy lithium vanadium phosphate precursor particles obtained in step (2) in a constant temperature drying oven at 100° C., weighing 50 g of the glassy lithium vanadium phosphate precursor and adding it to 15 g of starch in a ball mill for 10 hours to obtain a mixed powder containing the glassy precursor and a carbon source;

[0050] Step (4), placing the mixed powder after ball milling in step (3) in a tubular furnace with an argon atmosphere, heating it to 800°C at a rate of 15°C / min, calcining it at 800°C for 2h, and then cooling the material to room temperature at a rate of 80-100°C / min to obtain lithium vanadium phosphate material 1#, with a primary particle size of 10μm.

[0051] The lithium vanadium phosphate material 1# prepared in step (4) was subjected to TEM testing. The results showed that the TEM photo of the material was as follows: Figure 1 As shown in the figure, there are both a crystalline phase with clear lattice fringes and an amorphous phase without disordered fringes. Figure 1 The white dotted line in the middle is the amorphous phase area, and the rest of the areas with obvious lattice fringes are the crystalline phase areas, that is, the material has a structure in which crystalline and amorphous phases coexist; the white dotted line represents the carbon coating layer, that is, the lithium vanadium phosphate is uniformly coated with carbon.

[0052] Using lithium vanadium phosphate material 1# as the positive electrode active material, the following charge-discharge performance test was carried out.

[0053] Preparation of button cell 1#:

[0054] ① Take 9.2 g of lithium vanadium phosphate material 1# obtained in the example, grind and mix evenly with conductive agent Super-P: 0.4 g and binder PVD: 0.4 g, add NMP solvent, and stir for 6 hours to obtain electrode material slurry. The content of lithium vanadium phosphate material 1# in the electrode slurry is 92 wt%.

[0055] ②Evenly coat the electrode material slurry on the aluminum foil current collector and dry it in an oven at 85°C to obtain an electrode sheet. The surface density of the dry material on the electrode sheet is 7-10 mg / cm 2 .

[0056] ③ Cut the electrode sheet into discs, and use the lithium metal disc as the counter electrode to assemble button cell 1#.

[0057] The test conditions for button cell 1# are:

[0058] ① Voltage range: 2.8~4.3V, test environment temperature: 25℃, test current multiples are 1C, 6C, and 20C respectively.

[0059] ② Voltage range: 2.8~4.8V, test environment temperature: 25℃, test current multiples are 1C, 6C, and 20C respectively.

[0060] ③ Voltage range: 2.8~4.8V, test environment temperature: 25℃ charging, -30℃ discharging, the tested charging rate is 1C, and the current rates of low-temperature discharge are 1C, 2C, and 6C respectively.

[0061] The test results are:

[0062] Discharge capacity of button cell 1#:

[0063] 2.8~4.3V, 25℃, 125.5mAh / g at 1C rate, 123.4mAh / g at 6C rate, and 121.0mAh / g at 20C rate.

[0064] 2.8~4.8V, 25℃, 165.5mAh / g at 1C rate, 160.7mAh / g at 6C rate, and 148.1mAh / g at 20C rate.

[0065] 2.8~4.8V, charging at 25℃, discharging at -30℃, 140.2mAh / g at 1C rate, 135.8mAh / g at 2C rate, and 127.3mAh / g at 6C rate.

[0066] Comparative Example 1 Preparation of a single-phase polyanionic compound lithium vanadium phosphate (Li3V2(PO4)3)

[0067] The preparation process and conditions of the polyanionic compound lithium vanadium phosphate (Li3V2(PO4)3) are the same as those of the lithium vanadium phosphate material 1# in Example 1, except that the calcination time in step (4) is different. The specific details of the different steps are as follows:

[0068] Step (4), the mixed powder after ball milling is placed in a tubular furnace with an argon atmosphere, heated to 800°C at a rate of 15°C / min, calcined at 800°C for 10 hours, and then cooled to room temperature at a rate of 80-100°C / min to obtain lithium vanadium phosphate material A.

[0069] The lithium vanadium phosphate material A obtained in Comparative Example 1 was subjected to TME test. Figure 2 As shown, the results show that the obtained material has clear lattice fringes on the particles, all of which are crystalline phases, without any amorphous phase regions. It is pure crystalline lithium vanadium phosphate, and the pure crystalline lithium vanadium phosphate is uniformly coated with carbon.

[0070] The lithium vanadium phosphate material A obtained in Comparative Example 1 was used as the positive electrode active material to carry out a button battery performance test. The preparation and testing conditions of button battery A were the same as those of button battery 1# in Example 1. After testing, the discharge specific capacity of button battery A was:

[0071] 2.8~4.3V, 25℃, 114.0mAh / g at 1C rate, 101.2mAh / g at 6C rate, and 85.1mAh / g at 20C rate.

[0072] 2.8~4.8V, 25℃, 132.4mAh / g at 1C rate, 115.7mAh / g at 6C rate, and 92.0mAh / g at 20C rate.

[0073] 2.8~4.8V, charging at 25℃, discharging at -30℃, 90.1mAh / g at 1C rate, 78.5mAh / g at 2C rate, and 60.5mAh / g at 6C rate.

[0074] Example 2 Lithium manganese vanadium phosphate Li4MnV(PO4)3

[0075] The preparation process and conditions of the polyanionic compound lithium vanadium manganese phosphate Li4MnV(PO4)3 are the same as the preparation conditions of lithium vanadium phosphate material 1# in Example 1, except that the raw materials used in step (1) are different. The specific details of the different steps are as follows:

[0076] Step (1), accurately weigh 29.56g of lithium carbonate, 36.48g of vanadium phosphate, 21.74g of manganese dioxide, and 57.51g of ammonium dihydrogen phosphate, mix them evenly and add them into a corundum crucible, then place it in a muffle furnace and heat it to 1000°C, and calcine it to obtain a molten vanadium manganese lithium phosphate precursor.

[0077] The remaining steps were consistent with those in Example 1 to obtain lithium vanadium manganese phosphate material 2#. TEM testing showed that the material had a structure in which a crystalline phase and an amorphous phase coexisted, and the lithium vanadium manganese phosphate material was uniformly coated with carbon.

[0078] The lithium manganese vanadium phosphate material 2# was used as the positive electrode active material to conduct a button battery performance test. The preparation conditions and test conditions of button battery 2# were the same as those of button battery 1# in Example 1. After testing, the discharge specific capacity of button battery 2# was:

[0079] 2.8~4.3V, 25℃, 127.1mAh / g at 1C rate, 121.0mAh / g at 6C rate, and 117.5mAh / g at 20C rate.

[0080] 2.8~4.8V, 25℃, 170.8mAh / g at 1C rate, 165.2mAh / g at 6C rate, and 142.0mAh / g at 20C rate.

[0081] 2.8~4.8V, charging at 25℃, discharging at -30℃, 132.5mAh / g at 1C rate, 125.8mAh / g at 2C rate, and 120.1mAh / g at 6C rate.

[0082] Example 3 Lithium manganese silicate Li2MnSiO4

[0083] The preparation process and conditions of the polyanionic compound lithium manganese silicate Li2MnSiO4 are the same as the preparation conditions of lithium vanadium phosphate material 1# in Example 1, except that the raw materials used in step (1) are different. The specific details of the different steps are as follows:

[0084] Step (1), accurately weighing 40.64 g of lithium carbonate, 30.04 g of silica gel, and 21.74 g of manganese dioxide, mixing them evenly and adding them into a corundum crucible, then placing them in a muffle furnace and heating them to 900° C., and calcining them to obtain a molten lithium manganese silicate precursor;

[0085] The remaining steps were consistent with those in Example 1 to obtain lithium manganese silicate material 3#. TEM testing showed that the material had a structure in which a crystalline phase and an amorphous phase coexisted, and the lithium manganese silicate was uniformly coated with carbon.

[0086] The lithium manganese silicate material 3# was used as the positive electrode active material to carry out a button battery performance test. The preparation conditions of button battery 3# were the same as those of button battery 1# in Example 1, but the test conditions were different from those of button battery 1# in Example 1. The test conditions of button battery 3# were as follows:

[0087] ① Voltage range: 2.0~4.5V, test environment temperature: 25℃, test current multiples are 0.2C and 1C respectively.

[0088] ② Voltage range: 2.0~4.5V, test environment temperature: 25℃ charging, -30℃ discharging, the test charge rate is 0.2C, and the current rates of low temperature discharge are 0.2C and 1C respectively.

[0089] After testing, the discharge capacity of button battery 3# is:

[0090] 2.0~4.5V, 25℃, 124.0mAh / g at 0.2C rate, 120.5mAh / g at 1C rate.

[0091] 2.0~4.5V, charge at 25℃, discharge at -30℃, 108.2mAh / g at 0.2C rate, 100.5mAh / g at 1C rate.

[0092] Example 4 Sodium vanadium phosphate Na3V2(PO4)3

[0093] The preparation process and conditions of the polyanionic compound sodium vanadium phosphate Na3V2(PO4)3 are the same as the preparation conditions of lithium vanadium phosphate material 1# in Example 1, except that the raw materials used in step (1) are different. The specific details of the different steps are as follows:

[0094] Step (1), accurately weigh 42.40 g of sodium carbonate, 72.96 g of vanadium phosphate, and 28.76 g of ammonium dihydrogen phosphate, mix them evenly and add them into a corundum crucible, then place it in a muffle furnace and heat it to 1000° C. to obtain a molten sodium vanadium phosphate precursor.

[0095] The remaining steps were consistent with those in Example 1 to obtain sodium vanadium phosphate material 4#. TEM testing showed that the material had a structure in which a crystalline phase and an amorphous phase coexisted, and the sodium vanadium phosphate was uniformly coated with carbon.

[0096] Sodium vanadium phosphate material 4# was used as the positive electrode active material to carry out a button battery performance test. The preparation conditions of button battery 4# were the same as those of button battery 1# in Example 1, but the test conditions were different from those of button battery 1# in Example 1. The test conditions of button battery 4# were:

[0097] ① Voltage range: 2.0~4.5V, test environment temperature: 25℃, and the tested current multiples are 0.2C, 1C, 6C, and 20C respectively.

[0098] ② Voltage range: 2.0~4.5V, test environment temperature: 25℃ charging, -30℃ discharging, the test charge rate is 1C, and the low temperature discharge current rates are 0.2C and 1C respectively.

[0099] After testing, the discharge capacity of button battery 4# is:

[0100] 2.0~4.5V, 25℃, 110.2mAh / g at 0.2C rate, 109.5mAh / g at 1C rate, 107.6mAh / g at 6C rate, and 104.7mAh / g at 20C rate.

[0101] 2.0~4.5V, charging at 25℃, discharging at -30℃, 105.5mAh / g at 0.2C rate, 98.6mAh / g at 1C rate.

[0102] Example 5 Sodium manganese vanadium phosphate Na4MnV(PO4)3

[0103] The preparation process and conditions of the polyanionic compound sodium manganese vanadium phosphate Na4MnV(PO4)3 are the same as the preparation conditions of lithium vanadium phosphate material 1# in Example 1, except that the raw materials used in step (1) are different. The specific details of the different steps are as follows:

[0104] Step (1), accurately weigh 42.40g of sodium carbonate, 36.48g of vanadium phosphate, 21.74g of manganese dioxide, and 57.51g of ammonium dihydrogen phosphate, mix them evenly and add them into a corundum crucible, then place it in a muffle furnace and heat it to 900°C to obtain a molten sodium manganese vanadium phosphate precursor.

[0105] The remaining steps were consistent with Example 1 to obtain sodium manganese vanadium phosphate material 5#. TEM testing showed that the material had a structure in which a crystalline phase and an amorphous phase coexisted, and the sodium vanadium phosphate was uniformly coated with carbon.

[0106] Sodium manganese vanadium phosphate material 5# was used as the positive electrode active material to carry out a button battery performance test. The preparation conditions of button battery 5# were the same as those of button battery 1# in Example 1, and the test conditions were consistent with those of button battery 4# in Example 4.

[0107] After testing, the discharge capacity of button battery 5# is:

[0108] 2.0~4.5V, 25℃, 117.5mAh / g at 0.2C rate, 112.7mAh / g at 1C rate, 104.9mAh / g at 6C rate, and 98.5mAh / g at 20C rate.

[0109] 2.0~4.5V, charging at 25℃, discharging at -30℃, 109.5mAh / g at 0.2C rate, 100.2mAh / g at 1C rate.

[0110] Example 6 Sodium iron pyrophosphate Na2FeP2O7

[0111] The preparation process and conditions of the polyanionic compound sodium iron pyrophosphate Na2FeP2O7 are the same as the preparation conditions of lithium vanadium phosphate material 1# in Example 1, except that the raw materials used in step (1) are different. The specific details of the different steps are as follows:

[0112] Step (1), accurately weigh 116.51 g of sodium hydrogen pyrophosphate and 39.92 g of ferric oxide, mix them evenly and add them into a corundum crucible, then place it in a muffle furnace and heat it to 1000° C. to obtain a molten sodium iron pyrophosphate precursor.

[0113] The remaining steps were consistent with Example 1 to obtain sodium iron pyrophosphate material 6#. TEM testing showed that the material had a structure in which a crystalline phase and an amorphous phase coexisted, and the sodium iron pyrophosphate was uniformly coated with carbon.

[0114] Sodium manganese vanadium phosphate material 6# was used as the positive electrode active material to carry out a button battery performance test. The preparation conditions of button battery 6# were the same as those of button battery 1# in Example 1, and the test conditions were consistent with those of button battery 4# in Example 4.

[0115] After testing, the discharge capacity of button battery 6# is:

[0116] 2.0~4.5V, 25℃, 107.5mAh / g at 0.2C rate, 102.7mAh / g at 1C rate, 95.2mAh / g at 6C rate, and 65.2mAh / g at 20C rate.

[0117] 2.0~4.5V, charging at 25℃, discharging at -30℃, 95.2mAh / g at 0.2C rate, 80.3mAh / g at 1C rate.

[0118] Example 7 Sodium manganese pyrophosphate Na2MnP2O7

[0119] The preparation process and conditions of the polyanionic compound sodium manganese pyrophosphate Na2MnP2O7 are the same as the preparation conditions of lithium vanadium phosphate material 1# in Example 1, except that the raw materials used in step (1) are different. The specific details of the different steps are as follows:

[0120] Step (1), accurately weighing 122.07 g of sodium hydrogen pyrophosphate and 35.47 g of manganese oxide, mixing them evenly and adding them into a corundum crucible, and then placing the crucible in a muffle furnace and heating it to 900° C. to obtain a molten sodium manganese pyrophosphate precursor;

[0121] The remaining steps were consistent with Example 1 to obtain sodium manganese pyrophosphate material 7#. TEM testing showed that the material had a structure in which a crystalline phase and an amorphous phase coexisted, and the sodium manganese pyrophosphate was uniformly coated with carbon.

[0122] Sodium manganese pyrophosphate material 7# was used as the positive electrode active material to carry out a button battery performance test. The preparation conditions of button battery 7# were the same as those of button battery 1# in Example 1, and the test conditions were consistent with those of button battery 4# in Example 4.

[0123] After testing, the discharge capacity of button battery 7# is:

[0124] 2.0~4.5V, 25℃, 108.5mAh / g at 0.2C rate, 101.7mAh / g at 1C rate, 98.3mAh / g at 6C rate, and 68.8mAh / g at 20C rate.

[0125] 2.0~4.5V, charging at 25℃, discharging at -30℃, 92.6mAh / g at 0.2C rate, 74.5mAh / g at 1C rate.

[0126] Example 8 Sodium Titanium Phosphate NaTi2PO4

[0127] The preparation process and conditions of the polyanionic compound NaTi2PO4 are the same as those of the lithium vanadium phosphate material 1# in Example 1, except that the raw materials in step (1) are different. The specific details of the different steps are as follows:

[0128] Step (1), accurately weigh 29.20 g of sodium carbonate, 79.90 g of titanium dioxide, and 172.53 g of ammonium dihydrogen phosphate, mix them evenly and add them into a corundum crucible, then place it in a muffle furnace and heat it to 1000° C. to obtain a molten sodium titanium phosphate precursor.

[0129] The remaining steps were consistent with Example 1 to obtain sodium titanium phosphate material 8#. TEM testing showed that the material had a structure in which a crystalline phase and an amorphous phase coexisted, and the sodium manganese pyrophosphate was uniformly coated with carbon.

[0130] Sodium titanium phosphate material 8# was used as the positive electrode active material to conduct a button battery performance test. The preparation conditions of button battery 8# were the same as those of button battery 1# in Example 1, but the test conditions were different. The test conditions of button battery 8# were as follows:

[0131] Voltage range: 0.1~2.0V, test environment temperature: 25℃, and the tested current multiples are 0.2C, 1C, and 6C respectively.

[0132] After testing, the discharge capacity of button battery 8# is:

[0133] 0.1~2.0V, 25℃, 128.9mAh / g at 0.2C rate, 120.6mAh / g at 1C rate, 98.2mAh / g at 6C rate.

[0134] Example 9 Sodium vanadium trifluorophosphate Na3V2(PO4)2F3

[0135] The preparation process and conditions of the polyanionic compound sodium vanadium trifluorophosphate Na3V2(PO4)2F3 are the same as the preparation conditions of lithium vanadium phosphate material 1# in Example 1, except that the raw materials used in step (1) are different. The specific details of the different steps are as follows:

[0136] Step (1), accurately weigh 33.59 g of sodium fluoride, 72.96 g of vanadium phosphate, and 28.76 g of ammonium dihydrogen phosphate, mix them evenly and add them into a corundum crucible, then place it in a muffle furnace and heat it to 1000° C. to obtain a molten sodium vanadium trifluorophosphate precursor.

[0137] The remaining steps were consistent with Example 1 to obtain sodium vanadium trifluorophosphate material 9#. TEM test showed that the material had a structure in which a crystalline phase and an amorphous phase coexisted, and the sodium vanadium trifluorophosphate was uniformly coated with carbon.

[0138] Sodium vanadium trifluorophosphate material 9# was used as the positive electrode active material to conduct a button battery performance test. The preparation conditions of button battery 9# were the same as those of button battery 1# in Example 1, and the test conditions were consistent with those of button battery 4# in Example 4.

[0139] After testing, the discharge capacity of button battery 9# is:

[0140] 2.0~4.5V, 25℃, 119.7mAh / g at 0.2C rate, 115.0mAh / g at 1C rate, 108.2mAh / g at 6C rate, and 100.5mAh / g at 20C rate.

[0141] 2.0~4.5V, charging at 25℃, discharging at -30℃, 100.7mAh / g at 0.2C rate, 90.6mAh / g at 1C rate.

[0142] Example 10 Lithium vanadium phosphate Li3V2(PO4)3

[0143] The process and conditions of the polyanionic compound Li3V2(PO4)3 are the same as those of the preparation of lithium vanadium phosphate material 1# in Example 1, except that the calcination temperature in step (4) is different, which is 700°C. The specific details of the different steps are as follows:

[0144] Step (4), placing the mixed powder after ball milling in step (3) in a tubular furnace with an argon atmosphere, heating it to 700°C at a rate of 15°C / min, calcining it at 700°C for 2h, and then cooling the material to room temperature at a rate of 80-100°C / min.

[0145] The remaining steps are the same as those in Example 1, and lithium vanadium phosphate material 10# is obtained. According to TEM test, the material has a structure in which a crystalline phase and an amorphous phase coexist, and the lithium vanadium phosphate is uniformly coated with carbon.

[0146] The lithium vanadium phosphate material 10# was used as the positive electrode active material to conduct a button battery performance test. The preparation conditions and test conditions of button battery 10# were the same as those of button battery 1# in Example 1.

[0147] After testing, the discharge capacity of button battery 10# is:

[0148] 2.8~4.3V, 25℃, 120.1mAh / g at 1C rate, 118.4mAh / g at 6C rate, and 116.2mAh / g at 20C rate.

[0149] 2.8~4.8V, 25℃, 166.0mAh / g at 1C rate, 162.7mAh / g at 6C rate, and 144.0mAh / g at 20C rate.

[0150] 2.8~4.8V, charging at 25℃, discharging at -30℃, 138.2mAh / g at 1C rate, 133.1mAh / g at 2C rate, and 124.7mAh / g at 6C rate.

[0151] Example 11 Lithium vanadium phosphate material Li3V2(PO4)3

[0152] The process and conditions for preparing the polyanionic compound Li3V2(PO4)3 are the same as those for preparing the lithium vanadium phosphate material 1# in Example 1, except that the calcination time in step (4) is different. The specific details of the different steps are as follows:

[0153] Step (4), placing the mixed powder after ball milling in step (3) in a tubular furnace with an argon atmosphere, heating it to 800°C at a rate of 15°C / min, calcining it at 800°C for 1h, and then cooling the material to room temperature at a rate of 80-100°C / min.

[0154] The remaining steps are the same as those in Example 1 to obtain lithium vanadium phosphate material 11#. TEM test shows that the material has a structure in which a crystalline phase and an amorphous phase coexist, and the lithium vanadium phosphate is uniformly coated with carbon.

[0155] The lithium vanadium phosphate material 11# was used as the positive electrode active material to conduct a button battery performance test. The preparation conditions and test conditions of button battery 11# were the same as those of button battery 1# in Example 1.

[0156] After testing, the discharge capacity of button battery 11# is:

[0157] 2.8~4.3V, 25℃, 126.2mAh / g at 1C rate, 124.8mAh / g at 6C rate, and 120.3mAh / g at 20C rate.

[0158] 2.8~4.8V, 25℃, 154.5mAh / g at 1C rate, 140.2mAh / g at 6C rate, and 130.9mAh / g at 20C rate.

[0159] 2.8~4.8V, charging at 25℃, discharging at -30℃, 135.1mAh / g at 1C rate, 131.4mAh / g at 2C rate, and 120.9mAh / g at 6C rate.

[0160] Comparative Example 2: Pure Crystalline Lithium Vanadium Phosphate

[0161] The preparation process and conditions of the polyanionic compound lithium vanadium phosphate are the same as those of the preparation conditions of lithium vanadium phosphate material 1# in Example 1, except that the calcination conditions in step (4) are different. The specifics of the different steps are as follows:

[0162] Step (4), placing the mixed powder after ball milling in step (3) in a tubular furnace with an argon atmosphere, heating it to 800°C at a rate of 3°C / min, calcining it at 800°C for 3h, and then cooling the material to room temperature at a rate of 3°C / min.

[0163] The remaining steps are the same as those in Example 1 to obtain pure crystalline lithium vanadium phosphate B. XRD test results show that the obtained material is pure crystalline lithium vanadium phosphate.

[0164] Pure crystalline lithium vanadium phosphate B was used as the positive electrode active material to carry out a button battery performance test. The preparation conditions and test conditions of button battery B were the same as those of button battery 1# in Example 1.

[0165] After testing, the discharge capacity of button battery B is:

[0166] 2.8~4.3V, 25℃, 108.9mAh / g at 1C rate, 100.1mAh / g at 6C rate, and 91.0mAh / g at 20C rate.

[0167] 2.8~4.8V, 25℃, 129.5mAh / g at 1C rate, 110.3mAh / g at 6C rate, and 87.5mAh / g at 20C rate.

[0168] 2.8~4.8V, charging at 25℃, discharging at -30℃, 84.6mAh / g at 1C rate, 75.1mAh / g at 2C rate, and 55.0mAh / g at 6C rate.

[0169] Comparative Example 3 Crystalline lithium vanadium phosphate

[0170] The preparation of the polyanionic compound lithium vanadium phosphate is synthesized by direct one-time calcination, as follows:

[0171] Step (1), accurately weighing 32.52 g of lithium hydroxide monohydrate, 72.96 g of vanadium phosphate, 28.76 g of ammonium dihydrogen phosphate, and 20 g of starch, mixing them evenly using a ball mill, adding them into a corundum crucible, and then placing them in a tubular furnace in an argon atmosphere, heating them to 800° C., and calcining them for 15 hours to obtain a lithium vanadium phosphate material;

[0172] Step (2), ball-milling the obtained lithium vanadium phosphate material and sieving it through a 400-grid sieve;

[0173] Step (3), using XRD to analyze the screened lithium vanadium phosphate material to determine that the obtained material is pure crystalline lithium vanadium phosphate C.

[0174] Pure crystalline lithium vanadium phosphate C was used as the positive electrode active material to carry out a button battery performance test. The preparation conditions and test conditions of button battery C were the same as those of button battery 1# in Example 1.

[0175] After testing, the discharge capacity of button battery C is:

[0176] 2.8~4.3V, 25℃, 115.8mAh / g at 1C rate, 104.2mAh / g at 6C rate, and 95.2mAh / g at 20C rate.

[0177] 2.8~4.8V, 25℃, 140.0mAh / g at 1C rate, 114.9mAh / g at 6C rate, and 90.5mAh / g at 20C rate.

[0178] 2.8~4.8V, charging at 25℃, discharging at -30℃, 90.5mAh / g at 1C rate, 79.2mAh / g at 2C rate, and 64.5mAh / g at 6C rate.

Claims

1. A method for preparing a polyanionic material, characterized in that: Step (1), mixing raw materials containing an alkali metal source, a transition metal source, and an anion source, and calcining to obtain a molten precursor; Step (2), quenching the molten precursor to obtain amorphous particles; Step (3), mixing the amorphous phase particles with a carbon source, and ball milling to obtain a mixture; Step (4), calcining the mixture in an inert atmosphere to obtain the polyanionic material; The polyanionic material is composed of (X m O 3m+1 ) n- MO of anionic unit and polyhedral unit s and cationic units; The cationic unit is an alkali metal ion; The (X m O 3m+1 ) n- In the anion unit, X is selected from any one of P and Si; m=1 or 2; n=3 or 4; The MO of the polyhedral unit s wherein M is selected from at least one transition metal element; the transition metal is selected from V, Mn, Fe, and Ti; s=an integer from 4 to 8; The alkali metal ion is selected from Na + or Li + ; The alkali metal source is selected from at least one of sodium carbonate, sodium bicarbonate, sodium nitrate, sodium hydroxide, sodium acetate, disodium hydrogen phosphate, sodium pyrophosphate, sodium hydrogen pyrophosphate, sodium fluoride, lithium carbonate, lithium nitrate, lithium hydroxide, lithium acetate, lithium phosphate, and lithium fluoride; The transition metal source is selected from at least one of vanadium pentoxide, vanadium trioxide, vanadium dioxide, ammonium metavanadate, vanadium oxalate, vanadium phosphate, manganese dioxide, manganese pentoxide, titanium dioxide, ferric oxide, ferric oxalate, ferric acetate, and ferrous chloride; The anion source is selected from at least one of phosphoric acid, pyrophosphoric acid, ammonium hydrogen phosphate, ammonium pyrophosphate, ammonium hydrogen pyrophosphate, diammonium phosphate, lithium silicate, sodium silicate, and silica gel; In step (4), the heating rate of the roasting is 8-20°C / min, the roasting temperature is 700-1000°C, the roasting time is 1-2h, and the cooling rate after the roasting is 40-100°C / min.

2. The preparation method according to claim 1, characterized in that: The (X m O 3m+1 ) n- The anion unit is (PO4) 3- or (P2O7) 4- .

3. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of the amount of alkali metal in the alkali metal source, the amount of transition metal in the transition metal source, and the amount of X in the anion source is calculated based on the molar ratio of the alkali metal element, the transition metal element, and X in the obtained polyanionic material; The calcination temperature is 900-1150° C., and the calcination time is 1-10 hours.

4. The preparation method according to claim 1, characterized in that: In step (2), the cooling rate of the quenching is ≥80°C / min; The quenching is carried out by pouring the molten precursor into a quenching liquid; The quenching liquid is water.

5. The preparation method according to claim 1, characterized in that: In step (3), the carbon source is selected from at least one of citric acid, starch, glucose and sucrose; The amount of the carbon source is 15% to 45% of the amount of the amorphous phase particles; The ball milling time is 6 to 18 hours.

6. The preparation method according to claim 1, characterized in that: The inert atmosphere is argon; The particle size of the polyanionic material obtained in step (4) is 0.2-15 μm.

7. The polyanionic material obtained by the preparation method described in any one of claims 1 to 6.

8. The polyanionic material according to claim 7, characterized in that: The polyanionic material is selected from at least one of sodium vanadium phosphate, sodium manganese phosphate, sodium iron phosphate, sodium titanium phosphate, sodium vanadium trifluorophosphate, sodium iron trifluorophosphate, sodium manganese trifluorophosphate, sodium iron fluorophosphate, sodium manganese fluorophosphate, sodium vanadium fluorophosphate, sodium iron pyrophosphate, sodium iron pyrophosphate phosphate, sodium manganese pyrophosphate, sodium manganese phosphate pyrophosphate, sodium manganese silicate, sodium iron silicate, lithium vanadium phosphate, lithium vanadium manganese phosphate, lithium titanium phosphate, lithium vanadium fluorophosphate, lithium manganese silicate, sodium iron vanadium phosphate, sodium vanadium manganese phosphate, sodium iron vanadium fluorophosphate, sodium vanadium manganese phosphate, sodium iron vanadium manganese phosphate, sodium iron vanadium manganese phosphate, sodium iron vanadium manganese phosphate, sodium iron vanadium manganese phosphate, sodium iron vanadium manganese fluoride phosphate, sodium iron vanadium manganese fluoride phosphate, sodium iron vanadium manganese fluoride phosphate, sodium iron vanadium manganese fluoride phosphate, sodium iron vanadium manganese pyrophosphate, sodium iron vanadium manganese pyrophosphate, sodium iron vanadium manganese phosphate, sodium iron pyrophosphate, sodium iron vanadium manganese phosphate, sodium iron silicate, and sodium iron silicate.

9. The polyanionic material according to claim 7, characterized in that The polyanionic material contains disordered amorphous structures and ordered crystalline structures; the mass of the crystalline structures in the polyanionic material accounts for 50-90%; The surface of the polyanionic material is coated with carbon; The particle size of the polyanionic material is 0.2-15 μm.

10. Alkali metal battery positive electrode material, characterized in that The alkali metal battery positive electrode material contains the polyanionic material obtained by the preparation method according to any one of claims 1 to 6; or the alkali metal battery positive electrode material contains the polyanionic material according to any one of claims 7 to 9; the alkali metal battery is a lithium ion battery or a sodium ion battery.

Citation Information

Patent Citations

  • Method for preparing lithium vanadium phosphate positive electrode material

    CN106505197A

  • Lithium vanadium phosphate positive electrode material preparation method, and lithium vanadium phosphate positive electrode material and applications thereof

    CN108123108A